(untitled) (American International Journal of Biology and Life Sciences, 2019)
This study shows the bacteriological investigations of Diarrhoeal diseases among selected children who were between the ages of 0 – 14 years. Stool samples from primary school pupils in Akoko South West Local Government Area in Ondo State, Nigeria were used for this purpose. The organisms were isolated and identified using cultural and biochemical test. Isolates obtained were subjected to some antibiotic susceptibility testing. Out of total number of 120 samples examined only 40 (33.3%) of primary school pupils were found to have Diarrhoea associated with bacteria in which 17 (42.5%), 15 (42.5%), and 8(32.5%) were from 0-4 years, 5-9 years and 10-14 years respectively. The Bacteria species isolated include Escherichia coli were the most predominant microorganism. This is followed by Staphylococcus aureus, Bacillius cereus and Vibro cholerae respectively. As at the time of the study, there was significance difference between male and female gender with the male having high incidence of 55.0%. Among the antimicrobials used sparfloxacin and cefuroxime was most effective against Gram negative and Gram postive bacteria respectively. Also, most of the children tested were found to have common illness with clinical manifestations of diarrhoea followed by dysentery, abdominal pain and fever which may be accompanied with vomiting. Severity of infections varies with individual.